2016
DOI: 10.21276/sjams.2016.4.7.60
|View full text |Cite
|
Sign up to set email alerts
|

Study of Association Between Maternal 25 – hydroxy Vitamin D3 Level and Neonatal Outcome

Abstract: Abstract:The widespread global prevalence of hypovitaminosis D during pregnancy and its implications for undesirable health outcomes in present and future generations is an area of growing concerns. The study was undertaken with an aim to determine vitamin D status among pregnant women and their new-borns and to find association between maternal vitamin D level during pregnancy and neonatal outcome. This hospital based, observational study was conducted on 250 pregnant patients and their new-borns in departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…They concluded that maternal vitamin D status did not significantly affect neonatal anthropometry. Similar interpretation was made by Maghbooli et al 12 No major correlation was found amongst vitamin D concentration in cord blood and concentration of maternal vitamin D and the newborns' characteristics (length, head circumference, weight, diameter of anterior fontanel, diameter of posterior fontanel and APGAR score) and low birth weight. 15 In contrast to the above observations, Bowyer et al observed that subjects with deficient vitamin D had a decreased birth weight in newborns.…”
Section: Maghbooli Et Al Reported An Inverse Relationship Betweensupporting
confidence: 87%
See 2 more Smart Citations
“…They concluded that maternal vitamin D status did not significantly affect neonatal anthropometry. Similar interpretation was made by Maghbooli et al 12 No major correlation was found amongst vitamin D concentration in cord blood and concentration of maternal vitamin D and the newborns' characteristics (length, head circumference, weight, diameter of anterior fontanel, diameter of posterior fontanel and APGAR score) and low birth weight. 15 In contrast to the above observations, Bowyer et al observed that subjects with deficient vitamin D had a decreased birth weight in newborns.…”
Section: Maghbooli Et Al Reported An Inverse Relationship Betweensupporting
confidence: 87%
“…The mean age was found to be 24 years. 12 In the present study, the mean maternal ALP (r= -0.5503, Chi square=88.38, p=0.000) was significantly higher (114.30±15.59) in vitamin D deficient patients (p<0.05) with a weak negative correlation. As depicted in Table 4, maternal serum calcium bears a positive correlation with vitamin D levels which is statistically significant (r=0.7486, Chi square=137.53, p=0.000).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…The increasing use of multivitamins and mineral dietary supplements in younger to older adults does not appear to be associated with a corresponding increase in VD concentrations [36] and clinical guidelines suggest that doses of VD more than 600 IU/day may be needed to maintain adequate plasma levels, but the appropriate standard is still debated [37]. In some randomized controlled studies, loading doses as high as 1000e4000 IU/day were needed before adequate VD plasma concentrations were measured [38].…”
Section: Discussionmentioning
confidence: 99%
“…This improved bioavailability ensures that a greater proportion of the drug reaches the target site, enhancing therapeutic effectiveness. [ 5 ]…”
Section: Emerging Of In Situ Gelsmentioning
confidence: 99%